Echocardiographic right and left ventricular measurements in male elite endurance athletes - Henriksen, E.; Landelius, J.; Wesslen, L.; Arnell, H.; Nystrom-Rosander, C.; Kangro, T.; Jonason, T.; Rolf, C.; Lidell, C.; Hammarstrom, E.; Ringqvist, I.; Friman, G. (European Heart Journal, 1996)
Echocardiography was used to assess normal values in the right and left ventricular cavity and wall in 127 male elite endurance athletes. M-mode and two dimensional measurements of left ventricle and left and right atria were also obtained. All subjects were high-performance orienteers, cross-country skiers and middle-distance runners. They all had a normal electrocardiogram at rest and no echocardiographic evidence of heart disease. With the use of multiple right ventricular cross-sections and two-dimensional measurements, we found a significantly greater right ventricular inflow tract and right and left atrial measurements in endurance athletes compared with earlier studies of normal, active subjects. The right ventricular free wall was slightly thicker than reported in normal active subjects but the differences were small. Left ventricular diastolic diameter was consistent with previous reports of endurance athletes. Of the 127 subjects, 13% had left ventricular wall thickness above 13 mm but none of the athletes had wall thickness above 15 mm. These data suggest that cardiac enlargement occurs symmetrically in both right and left cavities, probably reflecting increased haemodynamic loading, a mechanism by which athletes sustain a high cardiac output during exercise.